Frequency of Esophageal Varices in Patients with Cirrhosis - Shahid, Muhammad; Inayat Ullah,; Ali, Farman; Abidduddin, (Indus Journal of Bioscience Research, 2025)
Background: Esophageal varices are a frequent and potentially life-threatening complication in patients with liver cirrhosis. Timely identification is crucial to preventing variceal bleeding and reducing morbidity. While risk stratification tools exist, their reliability varies, and demographic predictors remain inconclusive. Objective: To determine the frequency of esophageal varices in cirrhotic patients presenting to Lady Reading Hospital Peshawar. Study Design: Cross-sectional observational study. Duration and Place of Study: The study was conducted from September 2023 to March 2024 at the Department of Gastroenterology, Lady Reading Hospital, Peshawar. Methodology: A total of 131 adult patients with ultrasound-confirmed cirrhosis were enrolled based on clinical signs and radiologic findings. Patients with prior GI bleeding, variceal treatment, or hematologic conditions were excluded. All participants underwent upper GI endoscopy for the identification and grading of esophageal varices. Results: Most patients were male, and a high prevalence of esophageal varices was observed. Varices were graded as small, medium, or large based on established endoscopic criteria. No statistically significant associations were found between the presence of varices and patient age, gender, or cirrhosis duration. Conclusion: Esophageal varices are highly prevalent in cirrhotic patients, with no significant link to demographic factors.